111 Oxidative stress signalling through ask1 and P38-MAPK regulates cardiomyocyte gene expression and induces hypertrophy. (June 2018) - Rostron, Kerry; Meijles, Daniel; Cull, Joshua; Shaw, Spencer; Fuller, Stephen; Sugden, Peter; Clerk, Angela
Abstract : Background: Stress-regulated mitogen-activated protein kinases (SR-MAPKs; i.e. p38-MAPKs and JNKs) are activated by various stresses in the heart, causing cardiac dysfunction and cardiomyocyte death. Consequently, pathway components are potential therapeutic targets for heart failure. Cardiac ischemia is associated with increased oxidative stress that is further enhanced on reperfusion (I/R). Oxidative stress (e.g. H2O2) activates SR-MAPKs in cardiomyocytes and perfused hearts. However, ischemia selectively activates p38-MAPKs, with activation of JNKs by I/R. SR-MAPKs are activated by specific MAPK kinases (MKKs), but upstream MAP3Ks that initiate the signal in different conditions are not well-defined. The MAP3K, ASK1, is an oxidative stress-responsive activator of SR-MAPKs and is required for cardiac hypertrophy, but its specific role in ischemia or I/R is not clear. Our aims were to determine if ASK1 signals to SR-MAPKs in the heart during ischemia and/or I/R, and establish downstream consequences of ASK1 signalling. Methods/results: We confirmed that H2O2 activated SR-MAPKs in rat neonatal cardiomyocytes by immunoblotting with antibodies to the phosphorylated (activated) kinases. The concentration-dependence for ASK1 phosphorylation by H2O2 was bell-shaped, with maximal activation at 1 mM and reduced activation >1 mM H2O2. Rat hearts were perfused ex vivo and subjected to ischemia (15 min) or I/R (15/45 min). ASK1 was activated only during ischemia, consistent with moderate levels of oxidative stress being required. We did not detect activated ASK1 with I/R. Selonsertib (1 µM), a highly selective ASK1 inhibitor, suppressed activation of p38-MAPK (not JNKs) by H2O2 in cardiomyocytes or perfused hearts, or hearts subjected to ischemia or I/R. Thus, ASK1 signals selectively to p38-MAPK. The effects of 4 mg/kg/d selonsertib on mouse hearts (male C57Bl6; 10 weeks) in vivo were assessed with/without 0.8 mg/kg/d angiotensin II (AngII), a hypertensive model associated with increased oxidative stress (7 d; n=6–8). Echocardiography was used to assess cardiac function/dimensions. Selonsertib alone had no effect on any of the variables studied. AngII promoted cardiac hypertrophy with increased diastolic and systolic left ventricular posterior wall thickness. This was significantly inhibited by selonsertib indicating ASK1 is required in AngII-induced cardiac hypertrophy. Conclusions: ASK1 is an oxidative-stress responsive MAP3K that signals selectively to p38-MAPK in cardiomyocytes in the context of moderate stress during ischaemia. High level oxidative stress as occurs on reperfusion does not activate ASK1 to a significant degree. Moreover, ASK1 activation in hypertension contributes to the hypertrophic response. By dissecting upstream activators of p38-MAPK and JNKs, it will become apparent which may be targeted under specific conditions to manipulate p38-MAPK and/or JNK signalling for the management of heart failure.